Determination of optimal conditions for protease production from the local environmental bacteria Aeromonas hydrophila isolated from the surface waters of the Tigris River in Baghdad. (Journal of the College of Basic Education, 2022)
30 local isolates of Aeromonas hydrophila were isolated from 80 water samples, and the ability of the isolates to produce protease enzyme was tested using Skim milk agar. The optimum conditions for the production of the enzyme were determined, and the medium of liquid tryptone was the optimum medium for production at a pH of 7.5 after 24 hours of incubation at a temperature of 35 °C.